2020
DOI: 10.3390/cancers12102832
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals New Insights into the Immune Microenvironment and Upregulation of Novel Biomarkers in Metastatic Uveal Melanoma

Abstract: Metastatic uveal melanoma (mUM) to the liver is incurable. Transcriptome profiling of 40 formalin-fixed paraffin-embedded mUM liver resections and 6 control liver specimens was undertaken. mUMs were assessed for morphology, nuclear BAP1 (nBAP1) expression, and their tumour microenvironments (TME) using an “immunoscore” (absent/altered/high) for tumour-infiltrating lymphocytes (TILs) and macrophages (TAMs). Transcriptomes were compared between mUM and control liver; intersegmental and intratumoural analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 114 publications
5
35
0
Order By: Relevance
“…They performed NanoStringbased transcriptomic profiling of 40 mUM liver samples in comparison with 6 control liver specimens. They confirmed their preliminary data (Krishna et al, 2017;Figueiredo et al, 2020) by demonstrating that the M2 macrophage actively contributed to the immunosuppressive environment within the mUM and was characterized by the upregulation of AXNA1, CD74, CXCR4, MIF, STAT3, PLA2G6, and TGFB1 in addition to previously described genes, such as LGALS3 and HLA-DRA (Krishna et al, 2020). This study also revealed several novel genes that were upregulated by mUM, such as DUSP4, IRF4/MUM1, and CD44 (Krishna et al, 2020).…”
Section: Current Trends In Single-cell Technology For Uveal Melanomasupporting
confidence: 83%
See 2 more Smart Citations
“…They performed NanoStringbased transcriptomic profiling of 40 mUM liver samples in comparison with 6 control liver specimens. They confirmed their preliminary data (Krishna et al, 2017;Figueiredo et al, 2020) by demonstrating that the M2 macrophage actively contributed to the immunosuppressive environment within the mUM and was characterized by the upregulation of AXNA1, CD74, CXCR4, MIF, STAT3, PLA2G6, and TGFB1 in addition to previously described genes, such as LGALS3 and HLA-DRA (Krishna et al, 2020). This study also revealed several novel genes that were upregulated by mUM, such as DUSP4, IRF4/MUM1, and CD44 (Krishna et al, 2020).…”
Section: Current Trends In Single-cell Technology For Uveal Melanomasupporting
confidence: 83%
“…Although attempts have been made to improve our molecular understanding of the tumor microenvironment of UM by the microdissection of these subpopulations of cells and the application of NGS, these studies are still limited to the use of the bulk cells approach (Karlsson et al, 2020 ; Krishna et al, 2020 ).…”
Section: Current Trends In Single-cell Technology For Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…BAFF was able to promote the activities of B cells, CD4 + and CD8 + T cells [ 27 , 28 ]. Prior reports indicated that the tumor-infiltrating immune cells played a key role in the metastatic process of UM [ 18 , 29 , 30 , 31 , 32 ]. Besides the immune-associated mechanism, the BAFF gene was also reported to participate in the progression of malignancies through interacting with pluripotency-associated genes and epithelial mesenchymal transition (EMT)-associated genes [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of TILs is a marker of good prognosis for many cancers but not in UM where it is associated with a poor prognosis [ 57 , 58 ]. Why this is so is not fully understood, as there are contradictory reports on the immune cell subtypes populating liver metastases in UM [ 59 , 60 , 61 , 62 , 63 ]. It is of note that most studies that tried to characterize the immunosuppressive environment in UM metastases have been performed at the transcriptomic level on only very few immune cells.…”
Section: Immunobiology Of Uveal Melanomamentioning
confidence: 99%